Origin of the Large Entropy Change in the Molecular Caloric and Ferroelectric Ammonium Sulfate. (26th August 2022) - Yuan, Shurong; Meijer, Bernet E.; Cai, Guanqun; Dixey, Richard J. C.; Demmel, Franz; Dove, Martin T.; Liu, Jiaxun; Playford, Helen Y.; Walker, Helen C.; Phillips, Anthony E.
Abstract: The deceptively simple inorganic salt ammonium sulfate undergoes a ferroelectric phase transition associated with a very large entropy change and both electrocaloric and barocaloric functionality. While the structural origins of the electrical polarisation are now well established, those of the entropy change have been controversial for over 50 years. This question is resolved here using a combination of density‐functional theory phonon calculations with inelastic neutron scattering under variable temperature and pressure, supported by complementary total and quasielastic neutron scattering experiments. A simple model of the entropy in which each molecular ion is disordered across the mirror plane in the high symmetry phase, although widely used in the literature, proves to be untenable. Instead, the entropy arises from low‐frequency librations of ammonium ions in this phase, with harmonic terms that are very small or even negative. These results suggest that, in the search for molecular materials with functionality derived from large entropy changes, vibrational entropy arising from broad energy minima is likely to be just as important as configurational entropy arising from crystallographic disorder. Abstract : The large entropy change in ammonium sulfate, historically analyzed in terms of an order–disorder phase transition, is shown instead to arise from low‐frequency librations of ammonium molecules in flat‐bottomed energy wells. This suggests that similarly competing hydrogen‐bonded networks may be an attractive target for engineering new caloric molecular‐ionic materials.